2017
DOI: 10.1186/s12957-017-1144-1
|View full text |Cite
|
Sign up to set email alerts
|

IDH1 R132C mutation is detected in clear cell hepatocellular carcinoma by pyrosequencing

Abstract: Background Isocitrate dehydrogenase 1 (IDH1) mutation is common in low-grade glioma (approximately 80%) and acute myeloid leukemia (approximately 10%). Other than brain tumor or hematologic malignancies, intrahepatic cholangiocarcinoma (iCC) is a well-known solid tumor with IDH1 mutation (6.8–20%). Histologically, poor differentiation and clear cell change are associated with IDH1 mutation in iCC. Since hepatocellular carcinoma (HCC) shares histologic features with iCC, some specific subtypes of HCC might show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
0
21
2
Order By: Relevance
“…In this study, the average age of PCCCL patients was 64.1 years (range: 18-94 years), which was older than those reported by Qing-Yu Liu et al [14] (52 years) and Jung Hee Lee [25] (58.8 years). Regarding sex, our study indicated a male-to-female ratio of 1.43, indicating that males were more prone than females.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In this study, the average age of PCCCL patients was 64.1 years (range: 18-94 years), which was older than those reported by Qing-Yu Liu et al [14] (52 years) and Jung Hee Lee [25] (58.8 years). Regarding sex, our study indicated a male-to-female ratio of 1.43, indicating that males were more prone than females.…”
Section: Discussioncontrasting
confidence: 53%
“…Aggressive morphologic features and aneuploidy have been reported to be associated with the prognosis of PCCCL [44]. Clear cell HCC shows a higher frequency of IDH1 mutation, which is associated with shorter survival times [25]. Lack of such information limits our full understanding of PCCCL.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, D2HG accumulation as a result of loss-of-function mutations in D2HGDH has been observed in a small subset of large B-cell lymphoma 91 , implicating both the synthesis and conversion of D2HG in its accumulation in cancer. Using the cBioPortal Database 97 , <1% of IDH1/2 mutations are found in large-scale cancer genomic studies of RCC such as the TCGA dataset 97,98 . Although 2HG was identified to be significantly accumulated in human ccRCC tissues, >90% of this was in the L2HG isoform 99 , suggesting D2HG is unlikely to have a significant role in RCC pathogenesis.…”
Section: Pathogenesis Of Oncometabolite Accumulation Endogenous Origimentioning
confidence: 99%
“…Most studies comparing the prognosis of clear cell HCC versus conventional HCC showed a better prognosis of the former[55,56], or at least similar outcomes for both[57,58]. Interestingly, Lee et al[59] reported the presence of IDH1 mutation in 25% of clear cell HCC. These IDH1 mutated clear cell HCCs showed a statistically significant worse prognosis compared to IDH1 wild-type clear cell HCCs.…”
Section: Selected Subtypes Of Hepatocellular Carcinomamentioning
confidence: 99%